THE EQUIVALENCE AND SHIFTS IN THE INDONESIAN TRANSLATION OF ENGLISH PREPOSITIONS IN, ON, AND AT. - Noni - Marlianingsih (Universitas Nasional, 2015)
ABSTRACTThe aim of this study was to find out how the English prepositions in, on, and at are translated into Indonesian, and to describe the techniques used in translating. The method used in this research is descriptive qualitative. The data source were taken from the novel The Runaway Jury and its rendering in Indonesian entitled JuriPilihan. Based on this research, the English prepositions in, on, and at can be translated into Indonesian in the form of preposition. The results showed that there are three main categories namely in, on and at. The results show that the prepositions in English is 40% of the 100 data. English preposition on is 35% of the 100 data. The smallest amount, the English preposition at is 25% of the 100 data. Based on these results, we can conclude that the English prepositions in, on, and at can be translated into Indonesian become akan, dengan, di, ke, pada, tanpa, tentang, untuk, di, pada, selama, and mengenai.Key words: Equivalence, Shifts, Translation, PrepositionABSTRAK Tujuandaripenelitianiniuntukmencaritahubagaimanapreposisibahasainggrisin, on,danatditerjemahkankebahasa Indonesia, danuntukmenjelaskanteknik yang digunakan dalammenerjemahkan. Metode yang digunakandalampenelitianiniadalahkualitatifdeskriptif. Sumber data diambildari novel “The Runaway Jury”dantelahditerjemahkandalambahasa Indonesia berjudul “JuriPilihan”. Berdasarkanhasildaripenelitianini, preposisibahasainggrisin, on,danat dapatditerjemakankebahasa Indonesia dalambentukpreposisi. Hasilmenunjukkanbahwaadatigakategoriutamayaituin, ondanat. Hasil paling banyakdarianalisisinimenunjukkanbahwapreposisibahasainggrisinadalah 40% dari 100 data. Kedua, preposisibahasainggrisonadalah 35 % dari 100 data. Jumlahterkecil, preposisibahasainggrisatadalah 25 % dari 100 data. Berdasarkanhasiltersebut, sehinggadapatdisimpulkanbahwapersamaandaripreposisibahasainggrisin, on, danatdapatditerjemahkankebahasa Indonesia menjadiakan, dengan, di, ke, pada, tanpa, tentang, untuk, di, pada, selama, and mengenai.Kata kunci: persamaan, pergeseran, penerjemahan,preposisi